2007
DOI: 10.1080/02699050601151795
|View full text |Cite
|
Sign up to set email alerts
|

Children and young adults in a prolonged unconscious state after severe brain injury: Long-term functional outcome as measured by the DRS and the GOSE after early intensive neurorehabilitation

Abstract: More patients with TBI than expected reached a (semi-) independent level of functioning, indicating a possible effect of EINP. Patients suffering from nTBI did not demonstrate these outcome levels. Only a few patients stayed in a vegetative state for more than a couple of years. In this cohort of severe brain-injured young people, the DRS offered the best investigative possibilities for long-term level of functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 29 publications
3
29
0
1
Order By: Relevance
“…In light of these differences, outcomes and conclusions are understandably disparate across studies. For example, mortality rates for individuals with DOC range from 5 to 65%, with earlier studies and those from acute neurosurgical units yielding the highest rates of patient death (Braakman et al, 1998;Bricolo et al, 1980;Eilander et al, 2005Eilander et al, , 2007Estraneo et al, 2010;Fields et al, 1993;Giacino and Kalmar, 1997;Giacino et al, 1991;Heindl and Laub, 1996;Higashi et al, 1977;Lammi et al, 2005). Rates of recovery of consciousness range from 14 to 95% (Dubroja et al, 1995;Estraneo et al, 2010;Katz et al, 2009;Lammi et al, 2005;Luauté et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In light of these differences, outcomes and conclusions are understandably disparate across studies. For example, mortality rates for individuals with DOC range from 5 to 65%, with earlier studies and those from acute neurosurgical units yielding the highest rates of patient death (Braakman et al, 1998;Bricolo et al, 1980;Eilander et al, 2005Eilander et al, , 2007Estraneo et al, 2010;Fields et al, 1993;Giacino and Kalmar, 1997;Giacino et al, 1991;Heindl and Laub, 1996;Higashi et al, 1977;Lammi et al, 2005). Rates of recovery of consciousness range from 14 to 95% (Dubroja et al, 1995;Estraneo et al, 2010;Katz et al, 2009;Lammi et al, 2005;Luauté et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Existing studies vary in definition of DOC; setting (e.g., neurointensive care units vs. rehabilitation units); global region of health care provision (e.g., Europe vs. North America); study sample (e.g., children vs. adults, trauma vs. non-trauma, time since injury); length of follow-up; and outcomes evaluated (Braakman et al, 1998;Bricolo et al, 1980;Dubroja et al, 1995;Eilander et al, 2005Eilander et al, , 2007Estraneo et al, 2010;Fields et al, 1993;Giacino and Kalmar, 1997;Giacino et al,1991;Heindl and Laub, 1996;Higashi et al, 1977;Katz et al, 2009;Levin et al, 1991;Luauté et al, 2010;Ng and Chua, 2005). In light of these differences, outcomes and conclusions are understandably disparate across studies.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][30][31][32] As a whole, these studies have shown that patients who survive a TBI achieve greater functional and cognitive recovery than those with non-TBI 2, 3,9,[27][28][29]33 and that patients with anoxic brain injury have a similar rate of recovery compared with patients with TBI but have a worse outcome, as they tend to reach the upper limit of their potential more quickly than the former. 5,6,8,[30][31][32] However, many studies have not focused on severe ABI but instead included patients with a range of injury severity from mild to severe.…”
mentioning
confidence: 98%
“…Moreover, studies involving adult patients with severe ABI cannot be compared with studies that include children and young adults. 27,29 About the prognostic factors, the most commonly studied are age, 10,12,17,18,20,35,36 coma duration, 10,21 posttraumatic amnesia, 10,16 early rehabilitation, 22,[36][37][38] and functional and cognitive levels at admission. 12,[16][17][18]22,[39][40][41] Unfortunately, the results are sometimes contradictory 42,43 and thus only partially clear and congruent conclusions can be drawn and applied to clinical practice in the management of patients with severe ABI of different etiologies.…”
mentioning
confidence: 99%
See 1 more Smart Citation